2016
DOI: 10.4172/2378-5756.1000364
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiology of Aggression in Posttraumatic Stress Disorder

Abstract: Posttraumatic stress disorder (PTSD) is a universal anxiety disorder, affecting not only soldiers but also victims of every sort of traumatic stress-natural disaster, automobile collision, crime, domestic violence, bereavement. Aggressiveness, stemming from "intermittent explosive anger", is a not infrequent comorbidity of PTSD, with the most serious consequences. The neurophysiology of aggression and anger in general, and PTSD in particular, is a jigsaw puzzle of which we are first gathering the pieces. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 120 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that high-frequency electrical stimulation at the MeA mimics the effect of aggression priming on aggressiveness (Potegal et al, 1996a). High-frequency stimulation can induce NMDAR-dependent synaptic potentiation in various brain regions, including the MeA (Shindou et al, 1993;Watanabe et al, 1995Watanabe et al, , 1996Smerin et al, 2016). Therefore, it is possible that synaptic potentiation is involved in aggression priming.…”
Section: Low-frequency Photostimulation (Lfps) Of the Meapv Abolishesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that high-frequency electrical stimulation at the MeA mimics the effect of aggression priming on aggressiveness (Potegal et al, 1996a). High-frequency stimulation can induce NMDAR-dependent synaptic potentiation in various brain regions, including the MeA (Shindou et al, 1993;Watanabe et al, 1995Watanabe et al, , 1996Smerin et al, 2016). Therefore, it is possible that synaptic potentiation is involved in aggression priming.…”
Section: Low-frequency Photostimulation (Lfps) Of the Meapv Abolishesmentioning
confidence: 99%
“…A serious consequence of traumatic stress is PTSD, which has a lifetime prevalence of ;6%-8% (Kessler et al, 2005). It can be disabling and is characterized by persistent reexperiencing of traumatic events and hyperarousal symptoms, such as recurrent angry and aggressive outbursts (McHugh et al, 2012;Smerin et al, 2016). The mechanism for persistent and intrusive memories after traumatic events is emerging from clinical and animal studies (Desmedt et al, 2015).…”
Section: Traumatic Stress-induced Aggressionmentioning
confidence: 99%
“…For example, in rodents, stressful life experience such as social deprivation can instigate unprovoked attack behavior, and this effect is exacerbated by traumatic stress induced by foot shock (Veenema, 2009;Toth et al, 2011;Chang et al, 2015Chang et al, , 2018Zelikowsky et al, 2018;Chang and Gean, 2019). In humans, traumatic stress may trigger acute stress disorder and PTSD, and individuals with PTSD may exhibit increased aggression that lasts for years after the initial stressor (Nelson and Trainor, 2007;McHugh et al, 2012;American Psychiatric Association, 2013;Smerin et al, 2016;Taft et al, 2017). The neural circuits involved in traumatic stress-induced, prolonged aggression increase are largely unclear.…”
Section: Introductionmentioning
confidence: 99%